2002
DOI: 10.1525/maq.2002.16.1.22
|View full text |Cite
|
Sign up to set email alerts
|

"The Hands Know": Bodily Engagement and Medical Impasse in Highland Maya Bonesetting

Abstract: In southern Middle America, highland Maya bonesetters are called on to treat many cases of bodily injury. While Guatemalan Maya bonesetters vary greatly in their techniques and specialties, they prioritize manual treatment modalities, using their hands to address problems in clients' bodies. For bonesetters, the hands achieve direct knowledge of the suffering body, enabling them to work and securing the trust of those they treat. Nonetheless, Maya bonesetters face opposition from physicians who argue that bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Some of the sobadores say that they let the patient talk about the injury event because this relaxes them, but, beyond a general description of where the pain is felt, none of this appears to be considered necessary. This is similar to reports from South Texas [12], Mexico [11], and Guatemala [21]. Hinojosa reported that South Texas sobadores gained information from their tactile senses, understanding the patient’s conditions directly with their hands [12].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Some of the sobadores say that they let the patient talk about the injury event because this relaxes them, but, beyond a general description of where the pain is felt, none of this appears to be considered necessary. This is similar to reports from South Texas [12], Mexico [11], and Guatemala [21]. Hinojosa reported that South Texas sobadores gained information from their tactile senses, understanding the patient’s conditions directly with their hands [12].…”
Section: Discussionsupporting
confidence: 84%
“…Broken bones, in particular, most consider beyond the scope of their care. This contrasts with practice in Mexico, where sobadores are considered by some to be bonesetters [11, 21]. Indeed, Felipe reported that his first sobador experience in Mexico was setting a broken clavicle.…”
Section: Discussionmentioning
confidence: 98%
“…Intercorporeality is a form of intersubjectivity in which bodies communicate. The “laying on of hands” of Christian faith healers that Csordas () describes as an example of intercorporeality certainly has parallels with the Q'eqchi jilok technique and is a feature of Maya healing more generally (e.g., Hinojosa ). Indeed, there is a significant amount of physical and near‐physical contact between healers and patients; much of the therapeutic time is spent physically connected in one way or another.…”
Section: Therapeutic Communicationmentioning
confidence: 99%
“…Ācāṉs, on the other hand, dismiss radiography and imaging evidences, claiming that diagnosis of vital spots is a highly intricate process, only graspable by experienced practitioners. Admittedly, X‐ray records can serve a useful purpose with their before‐and‐after images of once‐broken bones, subsequently mended after therapy, and practitioners may sometimes keep scans that testify to their healing prowess (see Hinojosa :26). Nevertheless, ācāṉs generally say that vital spots are hidden and can be detected neither by scans nor by the eye, since neither pirāṇam nor vital spots are visible.…”
Section: Invisible Spots and Tracing The Secretmentioning
confidence: 99%